Сучасний погляд на таксономію роду Anemone L. sensu stricto (Ranunculaceae Juss.). Частина 2 - Ziman, S.N.; Bulakh, E.V.; Kadota, Yu. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
A key for definition of species, series, subsections, sections and subgenera of genera Anemone L. on the basis of the comparative analysis about of 70 characters of fruits, flowers, leaves, aboveground and underground shoots and roots is presented.